2016
DOI: 10.9790/0853-150740507
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lesions in Patients Attending Dermatology and STD/HIV Outpatient Department: Analysis of A Cohort of 300 Cases

Abstract: Background: The oral mucosa and tongue constitute a barometer, a mirror reflecting the state of health of patient. Similar to skin, lesions in mouth speak for itself. They often provide unique opportunity to understand systemic disease process. With careful and judicious practice many systemic diseases can be identified through the manifestations present in oral cavity. It is in light of this that it was thought proper to carry out a prevalence study of some of commonly occurring oral lesions in a skin, STD/HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
1
0
0
Order By: Relevance
“…This finding was similar to the studies done by Roy S et al, Arvind Babu RS et al [6,7]. On the contrary, studies done by Asia AJ et al and Shivakumar KM et al showed male preponderance with a male-to-female ratio of 1.41:1 and 1.53:1 respectively [8,9]. Female predilection might be due to their genetic susceptibility to the development of certain diseases.…”
Section: Discussionsupporting
confidence: 86%
“…This finding was similar to the studies done by Roy S et al, Arvind Babu RS et al [6,7]. On the contrary, studies done by Asia AJ et al and Shivakumar KM et al showed male preponderance with a male-to-female ratio of 1.41:1 and 1.53:1 respectively [8,9]. Female predilection might be due to their genetic susceptibility to the development of certain diseases.…”
Section: Discussionsupporting
confidence: 86%